Supplementation of Oxyrase in Extender Preserves Physico-Morphological Characteristics of Crossbred Hampshire Boar Semen - Katiyar, Rahul; Chakravarty, Himsikha; Dewry, Raju Kumar; Abedin, Sayed Nabil; Singh, Mahak; Rautela, Rupali; Kadirvel, Govindasamy; Deori, Sourabh (The Indian Journal of Animal Reproduction, 2022)
The aim of present study was to investigate the effect of Oxyrase, an oxygen scavenger, on sperm functional attributes in extended liquid preserved boar semen. In the experiment, we studied the effect of Oxyrase supplementation on sperm progressive motility, viability, functional integrity of sperm plasma membrane and acrosome integrity in Hampshire crossbred boars. The sperm functional parameters were assessed at 0, 3 and 5 d of incubation following Oxyrase supplementation (0.125 IU/mL). The results of study revealed that Oxyrase supplementation significantly (p
Keywords: Boar; semen; Oxyrase; sperm functional attributes; Hampshire